SURFACE-PROPERTIES OF ANTIMONY DOPED TIN(IV) OXIDE - A STUDY BY ELECTRON-SPECTROSCOPY - Cox, P; Egdell, R; Harding, C; Patterson, W; Tavener, P (1982)
Pure and antimony doped tin(IV) oxide (SnO2) have been studied by X-ray and ultraviolet photoelectron spectroscopy (XPS and UPS) and high resolution electron energy loss spectroscopy (HREELS). Pronounced surface enrichment by antimony in the doped material is evident from XPS, although both UPS and HREELS indicate that no increase in the free-carrier concentration close to the surface is associated with this segregation. Ultraviolet photoemission from undoped SnO2 is dominated by the filled O 2p valence band, the overall bandwidth being in good agreement with KKR calculations. However, a localized 5s-5p hybrid state associated with surface tin(II) ions gives rise to a feature in photoemission between the bulk conduction and valence bands. Carriers introduced by doping 3% antimony into the SnO2 lattice occupy a free-electron-like conduction band of predominantly metal 5s atomic character and may be observed directly in UPS. The Drude-like response of the conduction electrons produces a surface plasmon loss in low energy electron scattering spectra whose energy (0.55 eV) can be calculated from a simple free-electron model assuming an effective mass ratio close to unity. The localized electrons associated with surface antimony atoms are more tightly bound than electrons occupying the tin surface states; we speculate that this provides the thermodynamic driving force for surface enrichment in antimony. © 1982.